1998
DOI: 10.1093/emboj/17.20.6020
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin interaction mechanism of transcriptional control invivo

Abstract: We have used a kinetic analysis to distinguish possible mechanisms of activation of transcription of the different genes in the human beta globin locus. Based on in situ studies at the single-cell level we have previously suggested a dynamic mechanism of single genes alternately interacting with the locus control region (LCR) to activate transcription. However, those steady-state experiments did not allow a direct measurement of the dynamics of the mechanism and the presence of loci with in situ primary transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
2
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 44 publications
(85 reference statements)
3
66
2
3
Order By: Relevance
“…1B). Consistent with our earlier work (Gribnau et al 1998), the RNAPII elongation inhibitor DRB pro- Article is online at …”
supporting
confidence: 89%
See 1 more Smart Citation
“…1B). Consistent with our earlier work (Gribnau et al 1998), the RNAPII elongation inhibitor DRB pro- Article is online at …”
supporting
confidence: 89%
“…In this study we assessed RNAPII localization during short-term transcription inhibition to investigate these possibilities. DRB (5,6-Dichlorobenzimidazole 1-␤-D-ribofuranoside) specifically inhibits RNAPII elongation by inhibiting kinases that phosphorylate Ser2 of the C-terminal domain (CTD) of the large subunit of RNAPII (Fraser et al 1978;Marshall and Price 1995;Marshall et al 1996;Gribnau et al 1998). Heat shock at 45°C has been shown to globally inhibit transcription, disrupting both initiation and elongation (Hieda et al 2005).…”
mentioning
confidence: 99%
“…The role of NF-Y might instead be less direct, by modifying how the enhancers interact with the albumin promoter. Studies have suggested cycling of the distant LCR among the ⑀, ␥, and ␤ globin genes (23,24,65), and such cycling may occur in our dual promoter model. In the absence of NF-Y, dissociation of enhancer-promoter complexes during cycling might be slowed, which could reduce activity from both promoters.…”
Section: Discussionmentioning
confidence: 71%
“…Such behavior is not observed with plasmid models of the ␤-globin locus, where promoters compete for a common enhancer. These models combine normally distant transcription regulatory modules and so deal with only a limited aspect of long distance regulation in the ␤-globin locus (23,24). Nevertheless, the plasmid models establish two important properties of the promoters.…”
mentioning
confidence: 99%
“…In support of this, it has been shown that in transgenic mice harboring the human ␤-globin locus, while most cells in the fetal liver possess mRNA for both ␥ and ␤-globin, only a relatively small proportion display unspliced primary transcripts indicative of ongoing transcription of both genes (Wijgerde et al 1995). Further experiments have utilized DRB, a reversible inhibitor of transcriptional elongation (Gribnau et al 1998;Trimborn et al 1999). Upon release of fetal liver cells from DRB inhibition, a reproducible lag is observed in the reappearance of double signals, as compared to single signals indicating transcription from a single globin gene.…”
Section: How Do Lcrs and Enhancers Mediate Gene Activation Genes And Dementioning
confidence: 97%